Alternativas de Turismo de Base Comunitária na Amazônia Legal brasileira - Silvio Lima Figueiredo (Confins)
The study presents the results of research on the experiences of Community Based Tourism in the Brazilian Amazon, discussing the main characteristics of this type of practice through tourism concepts, the elaboration of the tourist social field, and its impacts on the regional development of the Amazon. The research demonstrates the main characteristics of the fourteen inventoried experiences, with the objectives, places of occurrence, the main activities carried out by each experience and the management characteristics. The study lasted from 2018 to 2021, based on field research and data available on websites for the dissemination of experiences. The result presents the diversity of types of experience, creating categories for analysis. It also informs the need to monitor concrete tourist practices, for scientific analysis and research on tourism and Community-Based Tourism.